1998
DOI: 10.1200/jco.1998.16.10.3264
|View full text |Cite
|
Sign up to set email alerts
|

Time to relapse has prognostic value in patients with aggressive lymphoma enrolled onto the Parma trial.

Abstract: Time to relapse may be used to stratify patients at time of first relapse of intermediate to high-grade non-Hodgkin's lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
2
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 22 publications
7
81
2
1
Order By: Relevance
“…Several groups have recently reported on prognostic features in patients with recurrent aggressive NHL. 4,[26][27][28] We confirmed that serum LDH provided strong independent prognostic information in patients with recurrent NHL. The association of disease stage with survival was less significant (P = 0.02) and there was a strong interaction of this parameter with phenotype (Table 4).…”
Section: Bone Marrow Transplantationsupporting
confidence: 65%
“…Several groups have recently reported on prognostic features in patients with recurrent aggressive NHL. 4,[26][27][28] We confirmed that serum LDH provided strong independent prognostic information in patients with recurrent NHL. The association of disease stage with survival was less significant (P = 0.02) and there was a strong interaction of this parameter with phenotype (Table 4).…”
Section: Bone Marrow Transplantationsupporting
confidence: 65%
“…Of particular importance, these responses are seen in a heavily pretreated population with several poor prognostic features such as chemo-resistant disease (Josting et al, 2000), relapse within a year (Brice et al, 1997;Guglielmi et al, 1998), advanced disease stage (Blay et al, 1998) and previous ASCT. Response to salvage chemotherapy is important prior to ASCT, as it is correlated with survival post-transplant (Philip et al, 1987;Brice et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for the relapse group, inclusion criteria were: refractory disease or end-of-treatment to relapse interval Ͻ1 year. 13,14,31 In addition, nine patients with aggressive lymphoma with at least two adverse prognostic factors according to the IPI, received this tandem protocol as first-line therapy after debulking chemotherapy with ACVBP induction. 7 In this group of patients, the remission rate is only 65% and tandem high-dose procedures may have a role in treatment strategies to improve the response rate and consolidation.…”
Section: Discussionmentioning
confidence: 99%